2019
DOI: 10.1002/ejoc.201900622
|View full text |Cite
|
Sign up to set email alerts
|

Renaissance of 1,2,5‐Oxadiazolyl Diazonium Salts: Synthesis and Reactivity

Abstract: A new approach for the synthesis and reactivity of the 1,2,5‐oxadiazolyl diazonium salts is represented. A simple and direct protocol to previously inaccessible furoxanyl and furazanyl diazonium salts was developed for the first time. Azo coupling reactions of thus obtained diazonium salts with a series of structurally diverse CH‐acids have been also successfully performed. Therefore, this study reveals new horizons for the use of furoxanyl and furazanyl diazonium salts in organic chemistry.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

1
13
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
4
1

Relationship

2
3

Authors

Journals

citations
Cited by 18 publications
(14 citation statements)
references
References 100 publications
1
13
0
Order By: Relevance
“…Diazotization of a substrate 1 a with NaNO 2 in acidic media followed by an azo coupling with KC(NO 2 ) 3 afforded target azasydnone 2 a in a low yield (entry 1), while other substituted nitromethanes were ineffective (entries 2–4). Utilization of t BuONO for diazotization was unsuccessful due to the very low nucleophilicity of the amino group in compound 1 a (entry 5) . NOBF 4 in TFA was a more effective diazotization system (entries 7–10).…”
Section: Methodsmentioning
confidence: 99%
See 4 more Smart Citations
“…Diazotization of a substrate 1 a with NaNO 2 in acidic media followed by an azo coupling with KC(NO 2 ) 3 afforded target azasydnone 2 a in a low yield (entry 1), while other substituted nitromethanes were ineffective (entries 2–4). Utilization of t BuONO for diazotization was unsuccessful due to the very low nucleophilicity of the amino group in compound 1 a (entry 5) . NOBF 4 in TFA was a more effective diazotization system (entries 7–10).…”
Section: Methodsmentioning
confidence: 99%
“…Utilization of tBuONO for diazotization wasu nsuccessful due to the very low nucleophilicityo ft he amino group in compound 1a (entry 5). [23] NOBF 4 in TFAwas am ore effective diazotization system (entries 7-10). Further solventa nd Lewis acid screening (see Ta ble S1 in the Supporting Information) indicated that an addition of AcOH and HCOOHw as required to increase the yield of azasydnone 2a,w hile ZnCl 2 (0.25 equiv) was the best catalystofc hoice (entry 10).…”
mentioning
confidence: 99%
See 3 more Smart Citations